Peningkatan Karakter Religius melalui Program Taqwa Character Building di SD Darul Hikam Bandung - Mubarok, Husni; Nikhlah, Sailin; Waroah, Lina Ulatul; Agustin, Annisa’ Qothrunnada; Alwi, Ahmad Akhsan; Himmah, Ihda Rifatul (Lembaga Yasin AlSys, 2022)
Man was created by Allah as a caliph because he has many gifts that other creatures have and do not have, it becomes a privilege and brings him to glory and happiness. Character is what distinguishes humans from animals. Humans can be called people who have strong characters and both individually and socially when they have good morals, morals, and character. The Taqwa Character Building program is used by researchers as a program to strengthen character education in schools which is thus related to student character or behavior. . In this TCB program there are three program structures starting from planning, process, and results, which later this program will be linked whether it can build students' morals or not. Darul Hikam's typical curriculum is one of Taqwa Character Building. Taqwa Character Building literally means building student character. SD Darul Hikam is one of the leading schools in Bandung which will become a postgraduate school through a long process with the initial stages of testing and development in the fields of human resources, facilities and infrastructure, infrastructure, environment, academic culture. Religious character is a person's special personality as a differentiator. between individuals with one another and obediently carry out the teachings of their religion. The 7 values of TCB are (sincere, patient, trustworthy, disciplined, caring, intelligent, and sincere) as the focus of character building for students whose goal is that students have the character of piety, namely obedient prayer.